Emplacement and 3D geometry of crustal-scale saucer-shaped intrusions in the Fennoscandian Shield - Buntin, Sebastian; Malehmir, Alireza; Koyi, Hemin; Hogdahl, Karin; Malinowski, Michal; Larsson, Sven Ake; Thybo, Hans; Juhlin, Christopher; Korja, Annakaisa; Gorszczyk, Andrzej (Scientific Reports, 2019)
Saucer-shaped intrusions of tens of meters to tens of kilometres across have been observed both from surface geological mapping and geophysical observations. However, there is only one location where they have been reported to extend c. 100 km laterally, and emplaced both in a sedimentary basin and the crystalline basement down to 12 km depth. The legacy BABEL offshore seismic data, acquired over the central Fennoscandian Shield in 1989, have been recovered and reprocessed with the main goal of focusing on this series of globally unique crustal-scale saucer-shaped intrusions present onshore and offshore below the Bothnian Sea. The intrusions (c. 1.25 Ga), emplaced in an extensional setting, are observed within both sedimentary rocks (1.5 Ga). They have oval shapes with diameters ranging 30-100 km. The reprocessed seismic data provide evidence of up-doming of the lower crust (representing the melt reservoir) below the intrusions that, in turn, are observed at different depths in addition to a steep seismically transparent zone interpreted to be a discordant feeder dyke system. Relative age constraints and correlation with onshore saucer-shaped intrusions of different size suggest that they are internally connected and fed by each other from deeper to shallower levels. We argue for a nested emplacement mechanism and against a controlling role by the overlying sedimentary basin as the saucer-shaped intrusions are emplaced in both the sedimentary rocks as well as in the underlying crystalline basement. The interplay between magma pressure and overburden pressure, as well as the, at the time, ambient stress regime, are responsible for their extensive extent and rather constant thicknesses (c. 100-300 m). Saucer-shaped intrusions may therefore be present elsewhere in the crystalline basement to the same extent as observed in this study some of which are a significant source of raw materials. Peer reviewed